Instagram Use and Mental Well-Being: The Mediating Role of Social Comparison. Issue 12 (December 2022) - Stefana, Alberto; Dakanalis, Antonios; Mura, Matteo; Colmegna, Fabrizia; Clerici, Massimo
Abstract: Instagram has grown in popularity among young adults and adolescents and is currently the second-favorite social network in the world. Research on its relationship to mental well-being is still relatively small and has yielded contradictory results. This study explores the relationship between time spent on Instagram and depressive symptoms, self-esteem, and disordered eating attitudes in a nonclinical sample of female Instagram users aged 18–35 years. In addition, it explores the mediating role of social comparison. A total of 1172 subjects completed a one-time-only online survey. Three different mediation analyses were performed to test the hypotheses that social comparison on Instagram mediates the association time spent on Instagram with depressive symptoms (model 1), self-esteem (model 2), and disordered eating attitudes (model 3). All three models showed that the relationship between intensity of Instagram use and the respective mental health indicator is completely mediated by the tendency for social comparison on Instagram.